The new Phlpost Corporate Center and National Postal Museum - Tobias, Mary Lorraine L.
The last thirty years of digital communication and e-commerce has brought the postal sector a declining role in mass information dissemination. Despite this, postal services currently remain relevant in the Philippines. The Philippines Postal Corporation remains steadfast in its goal of providing postal services anywhere in the country, which is strengthened by its membership in an extensive global network, partnerships, flexibility and adaptation to technology. This thesis explores the possibility of bridging the traditional functions of postal services and the future of postal architecture in relation to the advancement of communication. This is possible through highlighting the history of postal services in the country and incorporating newer functions and spaces most suitable to the current society, as evolved from the context of the traditional post office.